Diagnostic and prognostic implications of the PAX8–PPARγ translocation in thyroid carcinomas—a TMA‐based study of 226 cases. Issue 2 (6th June 2013) - Boos, Laura A; Dettmer, Matthias; Schmitt, Anja; Rudolph, Thomas; Steinert, Hans; Moch, Holger; Sobrinho‐Simões, Manuel; Komminoth, Paul; Perren, Aurel
Abstract : Aims: Follicular thyroid carcinoma (FTC) has been a diagnostic challenge for decades. The PAX8 – PPARγ rearrangement has been detected in FTC and classic papillary thyroid carcinomas (PTCs). The aims of this study were to assess the presence of PAX8 – PPARγ by using tissue microarrays in a large cohort of different thyroid neoplasms, and to assess its diagnostic and prognostic implications. Methods and results: Fluorescence in‐situ hybridization (FISH) analysis for PAX8–PPARγ was performed on 226 thyroid tumours, comprising FTCs ( n = 59), PTCs ( n = 126), poorly differentiated thyroid carcinomas (PDs; n = 34), follicular thyroid adenomas (FTAs; n = 5), and follicular tumours of unknown malignant potential (FTUMPs; n = 2). PAX8–PPARγ was detected in 12% of FTCs, 1% of PTCs, 7% of PDs, and in both cases of FTUMP. There was no correlation between the extent of capsular or vascular invasion and PAX8–PPARγ, or between lymph node or haematogenous metastasis and PAX8–PPARγ . Overall survival (OS), tumour‐specific survival (TSS) and relapse‐free‐survival (RFS) were not influenced by PAX8–PPARγ . Conclusions: In this study, we demonstrate for the first time the presence of PAX8–PPARγ in PDs and FTUMPs, whereas in FTCs and PTCs the prevalence of PAX8–PPARγ is lower than previously reported. PAX8–PPARγ did not correlate with invasiveness or affect prognosis in any tumour type.